Health Officer Behavior in Adolescent Caring Health Services (Adolescent Care Health Services) at the Health Center - Ita Alman Andela; Zahroh Shaluhiyah; Antono Suryoputro (Jurnal Penelitian Pendidikan IPA, 2023)
Health problems in adolescents are so complex, one of which is unwanted pregnancies due to the low level of preventive promotive efforts in adolescents that must be carried out by health workers through the Adolescent Care Health Services program.This study aims to describe the behavior of health workers in implementing the Adolescent Care Health Servicesprogram at the Kapus. A qualitative method with a case study approach has been used in this study, researchers used interviews and observations to answer the research objectives. Interviews were conducted with informants who were determined through a purposive sampling technique, then observations were made to determine the completeness of the facilities and guidelines owned by the officers.This study found that the behavior of officers in Adolescent Care Health Services services did not meet the good standards of predisposing factors, reinforcing factors and enabling factors. Another problem is the double workload, geographical conditions which are in difficult territory.For this reason, it is recommended that apparatus and leaders form innovations to increase cross-sector collaboration as an effort to overcome geographical problems by providing infrastructure in the village, increasing youth empowerment, and conducting outreach regarding the Adolescent Care Health Servicesprogram specifically for youth.